PEMBUATAN BAHAN AJAR DALAM BENTUK BROSUR MENGGUNAKAN MIND MAP UNTUK PEMBELAJARAN IPA SISWA KELAS VIII DI SMP NEGERI 8 PADANG - Mega Oktisa; Hidayati Hidayati; Pakhrur Razi (PILLAR OF PHYSICS EDUCATION, 2015)
Handout in brochure form use mind map is one of handout that can summarize learning material in simple form, so that students easier to connect facts in learning material, students can optimum thinking skill, understand learning material and can communication or told learning material that have they studied before by teacher. The purposes of this research were producing a high validity, a practicability and an effectivly of handout in brochure form use mind map. The type of research is Research and Development (R&D). The object of research was handout in brochure form use mind map and the subject of research was  students on grade VIII in Junior High School 8 Padang. The instruments that used to collect of data were the validation sheets, practicability sheets, and learning outcome sheets. The product and data analysis techniques that used were graphic method, description statistic analysis, and compare mean test. Based on the data analysis that has been done, it could be presented three research results. First, handout in brochure form use mind map on that produced has a high validity with an average value of lecture validity result of 83.88. Second, handout in brochure form use mind map were practice that indicated by the average value of physics teachers responses is  88.86 and 85.77 to average value of students responses. Three, implementing handout in brochure form use mind map was effective in Physics learning that indicated by increasing of significant learning on grade VIII of Junior High School 8 Padang before and after used handout in significant grade 5 %.